ERROR ANALYSIS OF INDONESIAN LEARNERS OF ENGLISH: A CASE STUDY OF THE BRITISH INSTITUTE CONVERSATION CLASS STUDENTS - Rahman, Rheza Nur (2014)
Tujuan utama dari studi ini adalah untuk mengidentifikasi kesalahan phonetic, morphology dan syntactic yang umum dilakukan oleh pelajar bahasa inggris di indonesia selama kelas percakapan. sampel yang diambil dalam studi ini adalah sebelas orang anggota kelas percakapan bahasa inggris level lima. kesalahan-kesalahan yang teridentifikasi dari sebelas orang anggota kelas percakapan bahasa inggris level lima di the british institute adalah penggantian konsonan /t/ untuk /ө/ dan /p/ untuk /f/; kegagalan penggunaan plural dan third person singular (-s/es), kesulitan besar dalam penggunaan derivational morpheme (-ment), progressive (-ing); dan kegagalan dalam penggunaan linking verb pada pembentukan kalimat progressive, kesulitan dalam penggunaan definite dan indefinite articles, serta kurangnya pemahaman dari subject-verb agreement.keywords: error analysis, second language acquisition Abstract The main purpose of this paper was to identify common phonetic, morphological, and syntactic errors committed by indonesian learner of english during the class conversation. the sample was eleven students of a level five english conversation class. these errors identified among eleven level five conversation class students of the british institute were substitution of consonant /t/ for /ө/ and /p/ for /f/; failure to use plural and third person singular (-s/es), the great difficulty in using derivational morpheme (-ment), progressive (-ing); and failed to use the linking verb in progressive construction, a difficulty in using definite and indefinite articles, and lack of subject-verb agreement.keywords: error analysis, second language acquisition